Mast Syndrome Outside the Amish Community: SPG21 in Europe - Amprosi, Matthias; Indelicato, Elisabetta; Nachbauer, Wolfgang; Hussl, Anna; Stendel, Claudia; Eigentler, Andreas; Gallenmüller, Constanze; Boesch, Sylvia; Klopstock, Thomas (Frontiers in Neurology, 2022)
Background: Mast syndrome is a rare disorder belonging to the group of hereditary spastic paraplegias (HSPs). It is caused by bi-allelic mutations in the ACP33 gene, and is originally described in Old Order Amish. Outside this population, only one Japanese and one Italian family have been reported. Herein, we describe five subjects from the first three SPG21 families of German and Austrian descent. Methods: Five subjects with complicated HSP were referred to our centers. The workup consisted of neurological examination, neurophysiological and neuropsychological assessments, MRI, and genetic testing. Results: Onset varied from child- to adulthood. All patients exhibited predominant spastic para- or tetraparesis with positive pyramidal signs, pronounced cognitive impairment, ataxia, and extrapyramidal signs. Neurophysiological workup showed abnormal motor and sensory evoked potentials in all the patients. Sensorimotor axonal neuropathy was present in one patient. Imaging exhibited thin corpus callosum and global brain atrophy. Genetic testing revealed one heterozygous compound and two homozygous mutations in the ACP33 gene. Conclusion: Herein, we report the first three Austrian and two German patients with SPG21, presenting a detailed description of their clinical phenotype and disease course. Our report adds to the knowledge of this extremely rare disorder, and highlights that SPG21 must also be considered in the differential diagnosis of complicated HSP outside the Amish community.